Shifting Maladaptive Fall Risk Appraisal in Older Adults through an in-Home Physio-fEedback and Exercise pRogram (PEER): A Pilot Study. Issue 4 (3rd July 2020) - Thiamwong, Ladda; Huang, Helen J.; Ng, Boon Peng; Yan, Xin; Sole, Mary Lou; Stout, Jeffrey R.; Talbert, Steven
ABSTRACT: Objectives: 1) examine the preliminary effectiveness of the P hysio-feE dback and E xercise pR ogram (PEER) for shifting maladaptive to adaptive fall risk appraisal and reducing fall risk, 2) determine the participants' feedback and acceptability of the program. Methods: Forty-one older adults were assigned to either PEER intervention or attention control group. The 8-week PEER intervention consists of a visual physio-feedback, cognitive reframing, and combined group and home-based exercise led by a trained peer coach. The attention control group read fall prevention brochures and continued their normal activities. BTrackS Balance Test (BBT), short version of Fall Efficacy Scale International (short FES-I) and CDC fall risk checklist were measured from pre- to post-intervention. The feedback and acceptability were conducted at the program conclusion. Results: About 11% of participants in the PEER group had positive shifting but none in the attention control group. Up to 32% of the participants in attention control had negative shifting compared to 5.3% in the PEER group. PEER group reported significant decreases in fall risk and high acceptability of the program. Conclusions: PEER intervention facilitates a shift from maladaptive to adaptive fall risk appraisal and reduces fall risk. Clinical Implications: Preventive interventions promoting alignment between perceive and physiological fall risk may contribute to reducing falls and increasing exercise adherence.